Economic and social satisfaction: The antecedents and consequence, and the moderating effect of brand strength in the context of retailer-manufacturer relationship in Yemen - Goaill, Majid Mapkhot'M (2014)
Available literatures have confirmed that there is a complex relationship between food manufacturers and large retailers especially in the growing strength of retail organizations in both the Yemeni and global contexts. To empirically investigate this relationship, the present study employed one single model of manufacturer-retailer relationship based on a review of the literature: (1) the impact of marketing relationship bonds on retailer‟s economic and social satisfaction; (2) the relationship between economic and social satisfaction, and their affect on commitment; and (3) the moderating effect of the manufacturer brands‟ strength on the relationships between retailer‟s economic and social satisfaction, and retailers‟ commitment. This quantitative study presents and discusses empirical findings from a survey of 140 independent large retailers using partial least squares-structural equation modeling (PLS-SEM). The findings of the study largely supported the hypothesized relationships proposed in the theoretical model. The results revealed that organizational bonds, but not interpersonal bonds, were crucial in affecting retailer‟s economic satisfaction. Meanwhile, interpersonal bonds were crucial in affecting retailer‟s social satisfaction. The results also provided strong evidence of the relationship between retailer‟s economic and social satisfaction, which in turn are necessary determinants of retailer‟s commitment. The study also found that the strength of manufacturer‟s brands enhanced the relationship between economic satisfaction and commitment, but not the relationship between social satisfaction and commitment. This study offers several implications on how managers of national food manufacturers can ensure the long-term success of their mutual business relationship with large retailers in light of the growing power of retailers. Additionally, this study suggests further research to compare the levels of large retailer‟s economic and social satisfaction with national and foreign suppliers, and investigate relational bonds in order to develop and maintain the national manufacturer‟s relationships with their marketing channels to achieve competitive advantage.